High salt diet accelerates skin aging in wistar rats: an 8-week investigation of cell cycle inhibitors, SASP markers, and oxidative stress - Peng, Xile; Liu, Nannan; Zeng, Baihan; Bai, Yilin; Xu, Yang; Chen, Yixiao; Chen, Li; Xia, Lina (Frontiers in Bioengineering and Biotechnology, 2024)
Background: Recent studies have shown that the high salt diet (HSD) is linked to increased dermal pro-inflammatory status and reduced extracellular matrix (ECM) expression in inflamed skin of mice. Decreased ECM content is a known aging phenotype of the skin, and alterations in ECM composition and organization significantly contribute to skin aging. This study aimed to determine whether a high salt diet accelerates skin aging and to identify the time point at which this effect becomes apparent. Methods: Wistar rats were randomly divided into normal diet and high salt diet groups and fed continuously for 8 weeks. Skin samples were collected at weeks 7 and week 8. Skin pathological sections were evaluated and levels of cell cycle inhibitors, senescence-associated secretory phenotype (SASP), oxidative stress and vascular regulatory factors (VRFs) were examined. Correlation analyses were performed to reveal the effect of a high-salt diet as an extrinsic factor on skin aging and to analyse the correlation between a high-salt diet and intrinsic aging and blood flow status. Results: At week 8, HSD rats exhibited thickened epidermis, thinned dermis, and atrophied hair follicles. The expression of cell cycle inhibitors and oxidative stress levels were significantly elevated in the skin of HSD rats at both week 7 and week 8.